2001
DOI: 10.1161/01.cir.103.13.1734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non–Insulin-Dependent Diabetes Mellitus on Myocardial Insulin Responsiveness in Patients With Ischemic Heart Disease

Abstract: In contrast to their peripheral tissues and coronary vasculature, the myocardium of patients with NIDDM expresses a competent insulin-response system with respect to glucose metabolism. This suggests that insulin resistance is mediated at the level of individual organs and that different mechanisms are involved in muscle and vascular tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 29 publications
7
58
1
1
Order By: Relevance
“…We previously observed that physiological hyperinsulinemia modestly increased coronary blood flow in subjects without diabetes (43), but that this effect was absent in patients with Type 2 diabetes who were studied under hyperglycemic conditions (20). In the present study, a 1-h glucose infusion induced endogenous insulin secretion.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…We previously observed that physiological hyperinsulinemia modestly increased coronary blood flow in subjects without diabetes (43), but that this effect was absent in patients with Type 2 diabetes who were studied under hyperglycemic conditions (20). In the present study, a 1-h glucose infusion induced endogenous insulin secretion.…”
Section: Discussionsupporting
confidence: 38%
“…Hyperglycemic patients with diabetes mellitus exhibit impaired endothelium-dependent vasodilatation in both the pe- ripheral (21,44) and coronary (20,37,43) circulation. Longitudinal studies have demonstrated this impairment to be associated with a substantially increased risk of adverse coronary events (2).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have not observed IR in hearts of type II diabetic patients, even when other diabetic tissues of the same patients exhibit significant IR (Utriainen et al, 1998;Jagasia et al, 2001). Thus under conditions of diabetic hyperinsulinemia, the less-resistant heart is being stimulated by relatively high levels of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin may also increase cardiac contractility (13) and may have an antiapoptotic effect on cardiomyocytes (14). In vivo, many of the effects of insulin on cardiac metabolism and function are related to the systemic effects of insulin, such as increased peripheral and coronary vasodilatation (15,16), increased sodium and water uptake by the kidneys (17), and changes in the delivery of substrates to the heart (18). For example, insulin's antilipolytic effect will reduce the delivery of FFAs to the heart, which, in concert with increased intracellular malonyl coenzyme A (CoA) levels, reduce fatty acid oxidation rates (19).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in myocardial glucose oxidation observed after insulin stimulation was unexpected and indicates, for the first time to our knowledge, that the ability of insulin to increase glucose oxidation in heart muscle might not be mediated by insulin receptors in the cardiomyocyte. Insulin receptors are present in the vascular endothelium (56), and insulin has been shown to be a potent vasodilator of the coronary vascular bed (16). Indeed, coronary flow was significantly higher in insulin-treated CIRKO animals than in controls.…”
mentioning
confidence: 99%